Pharmacotherapeutic response in drug use: Amitriptyline and Fluoxetine in the treatment of depression in the elderly (Research, Society and Development, 2022)
Objective: To carry out a literature review on the pharmacotherapeutic response in the use of the drugs Amitriptyline and Fluoxetine in the treatment of depression in the elderly. Methods: This is an exploratory bibliographic documentary study, of a qualitative nature, carried out in the Virtual Health Library databases, the Scientific Electronic Library Online (SciELO), Scientific Periodicals Electronic Library (SPELL), Portal of Periodicals of the Coordination of Higher Education Personnel Improvement (Capes), Latin American and Caribbean Literature in Health Sciences (LILACS), Public Medicine Library (PubMed) and Google Scholar, using the indexes: Depressive disorder; Pharmacotherapy; Amitriptyline; Fluoxetine; Pharmaceutical care. Thirty studies were selected between the period from 2012 to 2022. Results: Depression is a frequent disease in the elderly, its relationship is associated with a multifactorial set of factors that interfere with the quality of life of the elderly. physical, psychotherapy and occupational therapy, and pharmacotherapeutic intervention by antidepressants, Fluoxetine and Amitripline, used alone or in combination, require attention due to the pertinent comorbidities in the elderly patient. Conclusion: The studied antidepressants provide the increase or regulation of serotonin and norepinephrine concentration levels, the definition of dose adjustment depends on the pharmacotherapeutic response, which favor multiple effects to be considered. The pharmacist's co-participation is in the orientation and provision of information regarding the consumption and expected response of drug action, and the quantity and dose interval prescribed, contributing to the quality of life of the geriatric patient.